Combined analysis of the transcriptome and proteome of Eucommia ulmoides Oliv. (Duzhong) in response to Fusarium oxysporum - Lu, Yingxia; Dong, Xuan; Huang, Xiaozhen; Zhao, De-gang; Zhao, Yichen; Peng, Lei (Frontiers in Chemistry, 2022)
Eucommia ulmoides Oliv. (Duzhong), a valued traditional herbal medicine in China, is rich in antibacterial proteins and is effective against a variety of plant pathogens. Fusarium oxysporum is a pathogenic fungus that infects plant roots, resulting in the death of the plant. In this study, transcriptomic and proteomic analyses were used to explore the molecular mechanism of E. ulmoides counteracts F. oxysporum infection. Transcriptomic analysis at 24, 48, 72, and 96 h after inoculation identified 17, 591, 1,205, and 625 differentially expressed genes (DEGs), while proteomics identified were 66, 138, 148, 234 differentially expressed proteins (DEPs). Meanwhile, GO and KEGG enrichment analyses of the DEGs and DEPs showed that they were mainly associated with endoplasmic reticulum (ER), fructose and mannose metabolism, protein processing in the ER, type II diabetes mellitus, the ribosome, antigen processing and presentation, and the phagosome. In addition, proteome and transcriptome association analysis and RT-qPCR showed that the response of E. ulmoides to F. oxysporum was likely related to the unfolded protein response (UPR) of the ER pathway. In conclusion, our study provided a theoretical basis for the control of F. oxysporum.